Association of liana communities with their soil properties in a lowland forest of Negeri Sembilan, Peninsular Malaysia - Nizam, M.S; Nurfazliza, K; Nur Supardi, M.N (Universiti Kebangsaan Malaysia, 2012)
A study was conducted in a lowland forest at Pasoh Forest Reserve (FR), Negeri Sembilan, to determine the association between liana communities and its soil properties. Liana species inventory and soil samplings were carried out in 16 plots (40 m × 40 m each) established within the 50 ha permanent plot of Pasoh FR. All lianas with diameter at breast height (dbh) of 1 cm and above were measured, tagged and identified, whilst soil samples were analysed for texture, pH, base cations, available nutrients that include Mg, P and K, and inorganic nitrogen of ammonium-N and nitrate-N. The liana inventory recorded a total of 1628 individuals which comprised of 167 species and 65 genera from 31 families. The most speciose family was Annonaceae which was represented by 33 species, followed by Connaraceae and Leguminosae with 20 species and 19 species, respectively. Density-wise, the Leguminosae recorded the highest density of 41 stems/ha, whilst at species level, Byttneria maingayi (Sterculiaceae) showed the highest density of 25 stems/ha. The most important species based on the highest important value (IVi) was Byttneria maingayi with an IVi of 7.5%. Soils analyses showed that the soil texture was dominated by clay, and the organic matter content was low with mean percentage of 3.98±0.21%. In general, the soils of the study site were acidic, whilst available nutrients were in the range of low to high concentrations. Canonical Correspondence Analysis (CCA) showed a low species-environment correlation with eigenvalues of the first and second axes of 0.178 and 0.154, respectively. Nevertheless, the CCA species ordination diagram shows that several liana species are closely associated with soil factors such as soil pH, inorganic nitrogen and available nutrients of Mg, K and P, thus indicates the role of soil factors in influencing floristic distribution patterns of vegetation communities in the forest habitats